Improving food supply chain resilience: a case study of chicken tikka masala - Jones, Katharine; Garnett, Kenisha; Burgess, Paul J. (Cranfield University, 2025)
Food supply chain resilience can improve food security in the face of environmental disruptions such as climate change and disease outbreaks. There is a need to understand the how resilience is operationalised to clarify how businesses and governmental regulators can maintain and enhance resilience. This study seeks to understand how resilience is perceived and operationalised by food chain actors. Resilience strategies in a specific supply chain are investigated, focusing on chicken tikka masala manufactured by a small and medium enterprise (SME). A theoretical framework, based on robustness, recovery, and reorientation, is presented and applied to analyse resilience strategies. The research employs an embedded case study approach comprising surveys, interviews, and a workshop with supply chain actors across three tiers. Thematic analysis reveals that actors prioritise robustness and recovery strategies. Reorientation strategies, such as long-term adaptability and early warning systems, receive less focus due to perceived investment and capacity constraints, while visibility and collaboration are curtailed in SMEs with limited influence with larger actors. Key barriers include fragmented information flows, limited government policy alignment, and challenges of digital technology adoption. Recommendations include the need for policy consultation frameworks that improve policymakers’ understanding of food supply chains and actors’ decision-making processes.
Data comprises three methodological tools used in the study. These comprise: 1. Interview instrument : list of key questions and prompt questions used in semi-structured interviews 2. Survey instrument : list of survey questions in online survey completed by participants using Qualtrics 3. Plausible future scenarios: a set of four narrative scenarios produced for the online workshop incorporating qualitative data gathered through survey and interview responses describing possible future disruptions that could impact the supply chain. File format: .pdf/a Study data cannot be shared for ethical reasons.
Keywords: resilience; supply chain; environment; management; disruption; food; case study